Enzymatic transformation of aflatoxin B1 by Rh_DypB peroxidase and characterization of the reaction products. (July 2020) - Loi, Martina; Renaud, Justin B.; Rosini, Elena; Pollegioni, Loredano; Vignali, Elisa; Haidukowski, Miriam; Sumarah, Mark W.; Logrieco, Antonio F.; Mulè, Giuseppina
Abstract: In some environments, a number of crops, notably maize and nuts can be contaminated by aflatoxin B1 and related compounds resulting from the growth of aflatoxin-producing Aspergilli . Fungal peroxidases have been shown to degrade a number of mycotoxins, including aflatoxin B1 (AFB1 ). Therefore, the purpose of this study was to investigate the in vitro enzymatic degradation AFB1 by a recombinant type B dye decolorizing peroxidase (Rh_DypB). Analysis of the reaction products by HPLC-MS analysis showed that under optimized conditions AFB1 was efficiently transformed by Rh_DypB, reaching a maximum of 96% conversion after 4 days of reaction at 25 °C. Based on high resolution mass spectrometry analysis, AFB1 was demonstrated to be quantitatively converted to AFQ1, a compound with a significantly lower toxicity. A number of low molecular mass compounds were also present in the final reaction mixture in small quantities. The results presented in this study are promising for a possible application of the enzyme Rh_DypB for aflatoxin reduction in feed. Graphical abstract: Image 1 Highlights: Rh_DypB application could be of great interest for the treatment of contaminated feed. Rh_Dyp B peroxidase was applied for aflatoxin B1 biotransformation. Low enzyme and H2 O2 concentrations were effective to reduce Aflatoxin B1 . Aflatoxin B1 was quantitatively converted to Aflatoxin Q1 . AFQ1 has a lower acute toxicity and mutagenicity than AFB1 .